SISTEM BILANGAN POKOK TRADISIONAL DALAM MASYARAKAT NUSA TENGGARA TIMUR SEBUAH KAJIAN ETNOGRAFIS - Felysianus Sanga (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2010)
Every human species community has language. No matter whether they are primitive or not. A language certainly has numeral that covers primary numeral and derivative numeral. These two kinds of numeral as the basic aspect in arithmathic. The culture development of the ethnic group really depends on the language and the primary numeral. Based on the concept above. There was a question to be answered. “How is the variety system of the primary numeral formerly in East Nusa Tenggara spreads on more than 42 island. Every member of social group from East Nusa Tenggara knew the difference of this attitude and behavior. Although, it was difficult to know why and how there were difference and similarity. To answer the confusion, the society and the government really need a scientific research to be conducted professionally. This report was the result of the ethic and emic study with an ethnography approach by Spradley, “A development research sequence”. This research was conducted individually and it was known as the beginning research that covers only the way how to determine the ethic with its ethic and enmic. The finding shows that East Nusa Tenggara has 37 traditional social groups based on the way how to name the numeral. Furthermore, the groups were divided again into six groups based on the number of primary nmeral obtained